O discurso mêmico sobre o sujeito-professor em redes sociais - Silva, Andressa Cristina Oliveira da (2020)
When accessing social networks we come across many memes on various subjects and linked to events that occurred recently. By making the gesture of observing the activities of Internet users in the digital environment and also observing our activities when accessing networks, we understand that Internet users use memes in a humorous way to express opinions. Thus, used as a means of expressing opinion, memes are configured as an interesting object of analysis to understand the symbolic representations and the effects of meaning produced by the memes speech. This dissertation aims to understand the memes speech on social networks about the teacher-subject. We set as specific objectives (a) to approach basic notions of Discourse Analysis (AD), in an attempt to interpret the formulation, circulation and functioning of the object of study and (b) to analyze the possible effects of meaning and the functioning of memory in memes about the teacher-subject. The theoretical basis that supports this work is the Discourse Analysis of Franco-Brazilian orientation. We have delimited eleven memes that approach the representation of the teacher-subject and that circulated in the months of December 2018 to July 2019 as a clipping of the research. The composition of the corpus took place with the organization of a meme file, through access to social networks in the time frame, described above, and which represent the image of the teacher-subject, after the organization of the corpus, by our reading gesture, the memes were organized methodologically according to the discursive regularities they presented. For the organization of the corpus and analyzes, we mobilized the pendular movement between theory/analysis, to understand and analyze the imaginary representations produced about the teacher-subject, the effects of meaning and the relations of memory at work in memes. In an attempt to observe the movement of paraphrase present in memes that retake the imaginary representations that constitute the image of the teachersubject as a suffering subject. That, in our view, the imaginary representation of the teacher as a sufferer may be related to the historicity of the teaching profession in Brazil. With discussions and analyzes about imaginary representations in social networks about the teacher-subject, we collaborate for reflections on the teaching profession and its main protagonist, the teacher-subject.